THE EFFECT OF THE INCLUSION METHOD ON LEARNING AND RETAINING SOME BASIC VOLLEYBALL SKILLS - Muhannad Muhammed Kazem; Haider Taha Abdul Redha Mazloom (American Journals, 2023)
The research aimed to identify the effect of the (inclusion) method in learning and retaining some basic volleyball skills for students, comparing the (inclusion) method to the traditional commanding style method in learning and retaining some basic volleyball skills. The researchers used the experimental method because it suits the nature of the research problem, as the experimental method It gives real, tangible results about the impact of educational methods. As for the sample, it was randomly selected by lottery from among the classes, with two classes out of (4) classes, numbering (44) students. The number of members of the sample reached (38) students as well as (6) students practicing volleyball were excluded, they were divided into two groups: the experimental group, numbering 19 students, and the control group, numbering 19 students. Skill tests were conducted, including the facing serve test and the wall repetition test. The researchers reached the following results: the performance of the serve skill improved for the experimental group that was subjected to the curriculum. Educational method using the cooperative method. The performance of the skill of passing from above improved for the experimental group that was subjected to the educational curriculum using the cooperative method. There was fluctuation in the improvement of performance for the skill of serving and passing for the control group that was subjected to the educational curriculum using the traditional American method.
Keywords: Effect, inclusion method, learning and retaining.